Cu(I).Cu(III) Mixed Valence Complexes of Thiuram Disulfides of Triethylenetetramine Based Schiff Bases - Vijayanthimala, R.; Swathy, C.H.; Thangamariyammal, D. (Asian Journal of Chemistry, 2010)
Mixed valence Cu(I).Cu(III) complexes of thiuram disulphide formed from triethylenetetramine (trien) based Schiff bases have been isolated and characterized. Schiff bases are formed with salicylaldehyde, cinnamaldehyde, acetophenone, benzophenone and acetyl acetone. The complexes are characterized by elemental and thermal analysis, IR, UV-Visible, XPES studies. Magnetic studies indicate diamagnetic nature of the complexes.